Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction - Deo, Meenal S.; Mujawar, Sarfraj; Game, Onkar S.; Yengantiwar, Ashish; Banpurkar, Arun G.; Kulkarni, Sneha; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Nanoscale, 2011)
Cu2O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu2O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (similar to 120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction photo-response is far stronger as compared to that of a pulsed laser deposited thin film p-Cu2O/n-ZnO heterojunction, which can be attributed to higher junction area in the former case.